INTERTEXTUALITY IN INDONESIAN NEWSPAPER OPINION ARTICLES ON EDUCATION: ITS TYPES, FUNCTIONS, AND DISCURSIVE PRACTICE - Anni Holila Pulungan; Edi D. Subroto; Sri Samiati Tarjana; & Sumarlam (TEFLIN Journal: A publication on the teaching and learning of English, 2010)
Abstract: This research deals with intertextuality in opinion articles on education. Its objectives are to discover types and functions of intertextuality in the articles and to reveal its social practice. The results of the research reveal there are three major types and two major functions of intertextuality in the articles. The type dominantly applied is indirect quotation and the function dominantly applied is to provide things in detail. The social practice found in the articles is that the intertextuality is functioned to create an image that the articles possess a level of academic text.